Tantangan dan Eksistensi Madrasah Diniyah sebagai Entitas Kelembagaan Pendidikan Keagamaan Islam di Indonesia - Dwi Istiyani (Faculty of Education and Teacher Training, Institut Agama Islam Negeri Pekalongan, 2017)
This article explores the challenges and existence of madrasah diniyah (Islamic schools), one of Islamic educational institutions, that significantly contributes to the development of education in Indonesia. Nowadays, madrasah diniyah is classified into two categories, namely: madrasah diniyah takmiliyah (MDT/non-formal Islamic education) and formal diniyah/Islamic education (PDF). The existence of madrasah diniyah, as the entity of Islamic educational institutions in Indonesia, has found lots of challenges both externally and internally. Currently, the challenges in this respect are derived from the internal sector (the government/the Ministry of Education and Culture, the Republic of Indonesia). They refer to the government policy of full day school (FDS). This policy is deemed to have negative effects on eroding the existence of madrasah diniyah as the entity of Islamic educational institutions in Indonesia. Interestingly, those challenges motivate madrasah diniyah as educational institutions that emphasize social functions to communities, particularly village communities.